A Cidade dos Lázaros: isolacionismo, políticas públicas e lepra no Pará (1900-1934) - VIEIRA, Elis Regina Corrêa (Universidade Federal do Pará, 2025)
At the end of the XIX century and the beginning of XX, leprosy went through a process of singularization marked by an intense debate about etiology, therapy and prophylaxis of the disease. In this context, there was a theoric effort to consolidate leprosy as a disease caused by a bacillus and transmitted by contagion. At the same time, if the disease was contagious and its means of transmission was uncertain, the idea of isolating the patients was the only way of avoiding the spread of the disease became strength. In Brazil, many doctors and intellectuals participated in an international network of scientists that debated about the disease. In the same context, the health movement demanded that the Union increase its responsibilities in public health. The leprosy prophylaxis was benefited by these discussions and the federal government started to implement several leprosariums in partnership with the state government. Lazarópolis do Prata, in the state of Pará, was created in this context. It was installed in 1923 and officially opened in June 1924. My thesis proposes that doctors created a model of isolation to Lazarópolis, however, the experience of different individuals recreated the senses of this isolation, challenging the hygienist ideal of a kind, disciplined, and submissive "lázaro" to the doctors. Thus, even an institution seen as a model faced challenges such as escapes and violations to the established norms.